Response surface based co-optimization of release kinetics and mucoadhesive strength for an oral mucoadhesive tablet of cefixime trihydrate - Jagdish Manwar; Dipak D. Kumbhar; Ravindra Bakal; Swati Baviskar; Rahul Manmode (Faculty of Pharmacy, Cairo University, 2016)
Purpose: To design an oral mucoadhesive tablet of cefixime trihydrate using response surface methodology (RSM), and further to investigate the influence of formulation variables on drug release, and mucoadhesive strength. Methods: Tablets were prepared by direct compression method. A 23 factorial design was used to identify key independent variables affecting the drug release and mucoadhesive strength of formulation. The experimental data were analyzed statistically and the adequacy of fitted response was established through analysis of variance (ANOVA). The mechanism of drug release was investigated in detail by fitting the data to various kinetic models using PCP-DISSO V3 program. Results: Batch M3 showed the potential to retard the drug release and possessed significant mucoadhesive strength of 32.60 ± 0.1025 g. ANOVA results were substantiated by the Pareto analysis (p value <0.05) suggesting that the amount of carbopol (CP) 974P was the major factor affecting the studied responses. All the experimental batches followed either Higuchi or Peppas model and had release exponent (n) within 0.221-0.874. A distinct shift from fickian diffusion to anomalous transport of drug was noted with an increase in amount of CP 974P. Conclusion: Cefixime trihydrate can be effectively formulated as an oral controlled release mucoadhesive tablet using RSM, and it is possible to achieve adequate mucoadhesive strength and the desired release profile with the optimum combination of polymers.